Biometric Skin parameters in Individuals with Diabetes Mellitus: moisture, oiliness, elasticity, and pH (Estima – Brazilian Journal of Enterostomal Therapy, 2026)
Objective: To assess, through skin biometry, skin moisture, elasticity, oiliness, and pH in individuals with type 1 and type 2 diabetes mellitus. The evaluated regions included the forearm, palm and dorsum of the hands, leg, heel, and dorsum and plantar surface of the feet. The examination was performed before and after the use of a 10% urea-based cream. Method: This was an exploratory, longitudinal clinical study with a before-and-after design and no control group, conducted in primary healthcare units in the city of Pouso Alegre, Minas Gerais, Brazil. Thirty-four individuals participated in the study. Measurements were performed on days 0, 5, and 10 using the Digital Skin Analyser and a pH meter, model 6118 (Fujian WatapproveElectronic), following the application of a 10% urea cream. Results: The evaluated regions exhibited significant changes on different days of assessment. A marked improvement in skin elasticity and in the overall balance of cutaneous parameters was observed following the use of the cream. Conclusion: After 10 days of use of the 10% urea cream, skin biometry indicated improvements in moisture, oiliness, elasticity, and pH across the evaluated areas, demonstrating greater skin balance compared with the first day of assessment and supporting the applicability of the product as a simple and beneficial skincare measure.